Skills Mismatch in Rwanda’s TVET: Factors and Workforce Development Impacts - Faustin Ndikubwimana (Journal of Vocational Studies on Applied Research, 2026)
Technical and Vocational Education and Training (TVET) is central to Rwanda’s strategy for workforce development. However, evidence from policy documents, peer-reviewed literature, and international reports indicates a persistent skills mismatch between what TVET graduates offer and what employers need. This study synthesizes secondary data from 39 sources using a qualitative document analysis. The analysis identifies nine contributing factors to skills mismatch in Rwanda’s TVET sector, including outdated curricula, weak industry-institution collaboration, insufficient trainer competence, technological and infrastructure gaps, shortage of work-based learning, poor labor market information systems, limited entrepreneurial and soft skills training, funding and policy constraints, and socio-cultural barriers. These mismatches result in graduate unemployment, reduced organizational productivity, and constrained national growth. Based on the evidence, the study recommends modernizing the curriculum, expanding work-based learning, enhancing trainer development, strengthening industry partnerships, and improving labor market data systems. Due to the lack of primary data, findings are exploratory and should be validated through future tracer studies and employer surveys.